2022
DOI: 10.1007/s00405-022-07272-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of head orientation and implantation site of a novel transcutaneous bone conduction implant on MRI metal artifact reduction sequence

Abstract: Purpose The use of magnetic resonance imaging (MRI) is often limited in patients with auditory implants because of the presence of metallic components and magnets. The aim of this study was to evaluate the clinical usefulness of a customized MRI sequence for metal artifact suppression in patients with BONEBRIDGETM BCI 602 implants (MED-EL, Innsbruck, Austria), the successor of the BCI 601 model. Methods Using our in-house developed and customized metal art… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Prior studies have had variable success in reducing artifact with the Bonebridge implant despite the smaller transducer design in the newest version of the implant (BCI 602). 12,13 Prior studies demonstrated improvement in imaging quality with the use of metal mitigation sequences and placement of the implant in the middle fossa region, however, non-EPI DWI sequences were not evaluated. 13,14 The notable artifact in this implant is partially attributable to the diametric (and MR imaging conditional) magnet, which is not removable.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior studies have had variable success in reducing artifact with the Bonebridge implant despite the smaller transducer design in the newest version of the implant (BCI 602). 12,13 Prior studies demonstrated improvement in imaging quality with the use of metal mitigation sequences and placement of the implant in the middle fossa region, however, non-EPI DWI sequences were not evaluated. 13,14 The notable artifact in this implant is partially attributable to the diametric (and MR imaging conditional) magnet, which is not removable.…”
Section: Discussionmentioning
confidence: 99%
“…To a certain extent, the surgical technique will vary across surgeons; however, it should be noted that given the large area of artifact and distortion, differences in patient anatomy and surgical technique would be unlikely to dramatically change the results of the study. Similarly, the level of the artifact was not assessed with different head positions; Talon et al 12 found that head position did not change the quality of the MRI image with Bonebridge, and given that the area of the artifact is large, similar findings may be true of the Osia device. Further work will be required to assess this.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations